ROLE OF MRI IN EVALUATION OF SEIZURE DISORDER - SINGLA, NEERAJ; Singh, Jarnail; Kaur, Amarjit; K Badhan, Rajesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The present study was conducted to identify structural abnormalities on the brain imaging that may be associated with the cause of seizures and to study the spectrum of MRI findings in patients with seizures. Methods: This time-bound descriptive study was conducted on 100 seizure patients in the department of radiodiagnosis of GMC, Patiala. Informed consent was obtained and then MR imaging of brain was done. The results were analyzed. Results: Mean age was 39.59±15.96 years (range: 18–85 years) with 70% male and 30% female patients. The majority of the patients (80%) had generalized tonic–clonic seizures, followed by myoclonic seizures (8%), simple partial seizures (5%), complex partial seizures (2%), absence seizures (2%), motor seizures (1%), febrile seizures (1%), and tonic seizures (1%). The mean seizure duration was 2.15±1.48 months. On magnetic resource imaging (MRI), 44% patients had normal MRI. In remaining patients, MRI findings were infarct with gliosis (20%), ring enhancing lesions (18%), atrophy (6%), neoplasm (4%), thrombosis (3%), venous malformation (2%), and developmental malformations (3%). Conclusion: The most common type of seizures is GTCS. MRI can be normal in the majority of the patients of seizures. Common MRI abnormalities were infarct with gliosis and ring-enhancing lesions. Hence, MRI plays a significant role in the initial evaluation of seizures patients to rule out any organic or developmental lesions.